Throwing frame and performance of elite male seated shot-putters - Frossard, L.; O'Riordan, A.; Goodman, S. (Sports Technology, 2010)
Seated shot-putters rely on a customized assistive device called a throwing frame. Currently, the construction of each individual throwing frame is mainly driven by an empirical approach. One way to refine the conception is to improve the basic understanding of the performance of seated shot-putters. The relationship between performance and throwing technique has been well described. Remarkably, the relationship between performance and throwing-frame characteristics has received limited attention. The primary objective of this study was to present a cataloguing of characteristics of throwing frames used by seated shot-putters. This cataloguing consisted of defining and grouping 26 characteristics into three main categories (whole body, foot, and upper limb characteristics) and seven sub-categories. The secondary objective of this study was to provide raw characterisations of the throwing frames for a group of athletes who participated in a world-class event. The characterisations consisted of describing the characteristics of each throwing frame. Potential relationships between characteristics, performance, and classification were also identified. The cataloguing was achieved using a six-step heuristic approach, involving expert opinions and the analysis of 215 throwing attempts made by 55 male athletes during the 2006 IPC Athletics World Championships. The distribution of samples across characteristics suggested a relevant level of comprehensiveness for the proposed cataloguing. The raw data, the profile of best athletes, and the frequency of characteristics provided key benchmark information for construction of a throwing frame as well as coaching, classification, and officiating. Analysis of data sets relating to characteristics, performance, and classification were inconclusive.